2020
DOI: 10.1371/journal.pone.0242719
|View full text |Cite
|
Sign up to set email alerts
|

Instability-negative pressure loss model of gas drainage borehole and prevention technique: A case study

Abstract: The internal collapse of deep seam drainage borehole and negative pressure loss represents a serious technical problem affecting gas drainage. To address this problem a creep model of coal around borehole was established based on the plastic softening characteristics of coal. The final collapse time of the borehole was determined and used to derive the three stages of the borehole collapse process. The model of negative pressure loss in drainage borehole was established according to the theory of fluid dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Under the action of long-term axial loading, the porous specimens were subjected to internal sprouting, expansion, evolution of microfractures, and finally formation of penetration cracks leading to damage. Based on the results of the graded loading creep experiments on porous specimens in this paper, it is found that there is a relationship between creep damage and creep strain in coal rock materials [ 29 , 30 ]. According to the definition of the damage variables, the creep strain at each stage of the creep process is taken as the damage variable of the specimen, and assuming that the damage variable is 1 when the specimen is damaged and the coal rock is in a non-damaged state when the water content is 0%, the creep strain damage variable of the coal rock material is written as [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Under the action of long-term axial loading, the porous specimens were subjected to internal sprouting, expansion, evolution of microfractures, and finally formation of penetration cracks leading to damage. Based on the results of the graded loading creep experiments on porous specimens in this paper, it is found that there is a relationship between creep damage and creep strain in coal rock materials [ 29 , 30 ]. According to the definition of the damage variables, the creep strain at each stage of the creep process is taken as the damage variable of the specimen, and assuming that the damage variable is 1 when the specimen is damaged and the coal rock is in a non-damaged state when the water content is 0%, the creep strain damage variable of the coal rock material is written as [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…He JF [ 45 ] conducted research on large-diameter boreholes and demonstrated their effectiveness in gas extraction from deep soft coal. Qi QJ [ 46 ] addressed the issues of borehole collapse and negative pressure loss in deep gas drilling by proposing a technique that used a full-hole deep-screen wire mesh for extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Di et al [35] proposed the regional solidification pore formation method for soft coal seams, which can solidify the strength of the rock surrounding the borehole and improve the pore formation rate. Qi et al [36] tested the full-hole deep screen mesh tube drainage technology to solve the problem of internal collapse and negative pressure loss of deep coal seam drainage boreholes, which can effectively control the collapse and deformation of boreholes and reduce the negative pressure loss. Compared with conventional drainage, after 90 days, the gas drainage concentration increased by 101% and the gas flow increased by 97%, so the gas drainage rate increased significantly.…”
Section: Introductionmentioning
confidence: 99%